2011
DOI: 10.1074/jbc.m111.247866
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Nuclear Factor 1α (HNF1α) Dysfunction Down-regulates X-box-binding Protein 1 (XBP1) and Sensitizes β-Cells to Endoplasmic Reticulum Stress

Abstract: Correct endoplasmic reticulum (ER) function is critical for the health of secretory cells, such as the pancreatic ␤-cell, and ER stress is often a contributory factor to ␤-cell death in type 2 diabetes. We have used an insulin-secreting cell line with inducible expression of dominant negative (DN) HNF1␣, a transcription factor vital for correct ␤-cell development and function, to show that HNF1␣ is required for Xbp1 transcription and maintenance of the normal ER stress response. DN HNF1␣ expression sensitizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…Dose–response experiments demonstrated that chronic treatment with 0.5 μM CPA abrogated the early reduction in cytosolic Ca 2+ observed in cell models and primary neurons and prevented subsequent Ca 2+ increase and ensuing AS aggregation‐dependent cell death. The effective CPA concentration of 0.5 nM was low compared to what is used to induce unfolded protein stress in cell models , and it was not toxic to our cell models even after treatment for more than 2 weeks. This was expected because low‐dose long‐term pharmacological inhibition of SERCA with thapsigargin that causes a sustained increase in cytosolic Ca 2+ protects against neuronal cell death due to growth factor removal .…”
Section: Discussionmentioning
confidence: 78%
“…Dose–response experiments demonstrated that chronic treatment with 0.5 μM CPA abrogated the early reduction in cytosolic Ca 2+ observed in cell models and primary neurons and prevented subsequent Ca 2+ increase and ensuing AS aggregation‐dependent cell death. The effective CPA concentration of 0.5 nM was low compared to what is used to induce unfolded protein stress in cell models , and it was not toxic to our cell models even after treatment for more than 2 weeks. This was expected because low‐dose long‐term pharmacological inhibition of SERCA with thapsigargin that causes a sustained increase in cytosolic Ca 2+ protects against neuronal cell death due to growth factor removal .…”
Section: Discussionmentioning
confidence: 78%
“…TUDCA could inhibit ER stress induced by thapsigargin, and restore the decreased glucose stimulation index of islets ( Lee et al, 2010 ). TUDCA could also partially rescue dominant negative HNF1α-induced ER stress in β-cells ( Kirkpatrick et al, 2011 ). Most lately, it was reported that TUDCA prevented high glucose-induced β-cells dysfunction and reduced ER stress markers ( Tang et al, 2012 ).…”
mentioning
confidence: 97%
“…It has been reported that transcription factors other than ATF6 induce Xbp1 expression. For example, HNF1α and HNF4α were found to induce Xbp1 expression in pancreatic β-cells [38,39].…”
Section: Discussionmentioning
confidence: 99%